2018
DOI: 10.1177/0748233718799191
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity assessment of perfluoroalkyl substances on human sperm

Abstract: Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are synthetic chemicals that have been used in industry and consumer products. Because the presence of PFAS has been identified in humans and the environment in the last decade, human exposure to PFAS is a current public health concern. It has been shown that some PFAS lead to adverse health effects in the male reproductive system. However, there is no information about probable genotoxic effects of these chemicals on sperm cells. This study aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…PFASs, such as PFOA and GenX, are compounds with carbon-fluorine bonds that are commonly used in the manufacturing industry (Prevedouros et al, 2006). However, the accumulation of PFASs in the body causes multiple toxicities, including immunotoxicity, genetic toxicity, neurotoxicity, and hepatotoxicity (DeWitt et al, 2019;Emerce and Çetin, 2018;Fletcher et al, 2019;Gaballah et al, 2020;Ojo et al, 2020;Shane et al, 2020;Sun et al, 2019;Wen et al, 2020). In this study, we used hepG2 cells to demonstrate that GenX induces apoptosis in liver cells.…”
Section: Discussionmentioning
confidence: 93%
“…PFASs, such as PFOA and GenX, are compounds with carbon-fluorine bonds that are commonly used in the manufacturing industry (Prevedouros et al, 2006). However, the accumulation of PFASs in the body causes multiple toxicities, including immunotoxicity, genetic toxicity, neurotoxicity, and hepatotoxicity (DeWitt et al, 2019;Emerce and Çetin, 2018;Fletcher et al, 2019;Gaballah et al, 2020;Ojo et al, 2020;Shane et al, 2020;Sun et al, 2019;Wen et al, 2020). In this study, we used hepG2 cells to demonstrate that GenX induces apoptosis in liver cells.…”
Section: Discussionmentioning
confidence: 93%
“…Prior reviews reported that PFAS are not directly mutagenic and suggested that the DNA damage observed in some assays is likely a secondary event resulting from oxidative damage [47]. Recent toxicological studies reported similar findings for legacy and long-chain PFAS as well as the replacement and short-chain PFAS, GenX and PFBS [4,48,59,60]. Additionally, 28 day toxicity studies published by the National Toxicology Program for the carboxylates, PFOA, PFHxA, PFNA and PFDA and the sulfonates, PFOS, PFHxS, and PFBS, found no indication of genotoxicity in vivo or in vitro [61,62].…”
Section: Is Genotoxicmentioning
confidence: 89%
“…Similarly, Joensen et al reported equivalent results in their 2009 study with PFOA and PFOS (129), but these outcomes could not be reproduced in their later study published in 2013 (131), possibly due to lower levels of PFAS recorded in this later cohort (0.5% for PFOS), in which no participants were classified in the 'high exposure' category as per the criteria in the first study. Further studies also failed to find an association between PFAS and sperm quality (132,133,(135)(136)(137); thus precluding the establishment of causative links (133,136). Sperm motility has also been found to correlate both positively and negatively with PFOA exposure.…”
Section: Known Effects Of Pfas Exposure On Male Fertilitymentioning
confidence: 98%